KAJIAN KESESUAIAN LAHAN SECARA FISIK UNTUK TANAMAN CENGKIH DI DESA TENGA KECAMATAN TENGA - Vesrter J. Worung; Jody M. Mawara; Karamoy Lientje Th. (COCOS, 2020)
ABSTRACKVester J. Worung. 13031108059. Physical Land Suitability Study For ClovePlants in Tenga Village, Tenga District. Under the Guidance of Dr. Ir. Jody M.Mawara, M.Si (Chair) and Dr. Ir. Lientje Th. Karamoy, M.Si (Member).This study aims to evaluate the leval of land suitability for clove plants in thestudy area and the factors that limit them, and to determine the distribution of thesuitability of clove plantations in the study area. This research is excpected to beuseful to provide information to farmers in the middle region and the local govermantabout land characteristic and land suitability so that it can contribute to planning landuse for cloves plants.The method used in this research is a descriptive survey method that isdirectly observed in the field, namely soil depth, soil drainage, erosion, flood hazards,surface rocks, slope, rainfall, air humidity and temperature obtained from BMKG(Meteorology and Geophysics Agency) while the soil texture is determined in thefield by feeling and soil permeability. Retrieval of land characteristics ini the fieldusing the land unit approach.The results showed that the actual land suitability class for clove plants inTenga Village, Tenga District was obtained : S1 class (very suitable) on land unitsV1 (LaIIKl), V3 (LaIKl) and V4 (LaIIIKl) land area of 1.450 ha (31,73 %); S3 class(marjinal suitable) on land unit V5 (LaIVKl) land area of 720 ha (15,75 %) ; N class(not suitable) on land units V2 (LaVKl), V6 (LaVIKl) and V7 (LaVKl) covering anarea of 2,400 ha (52,52 %) with limiting erosion hazard factors (eh) especially theslope factor.3Pay attention to limiting factors in the land unit V2 (LaVKl), V6 (LaVIKl),dan V7 (LaVKl) covering on area of 2,400 h (52,52 %) the risk of erosion (eh)especially the slope factor, then after efforts are made to repair the soil or benchesterraces, individual terraces on clove plants, planting ground cover crops, to protectfrom rainwater that falls directly to the ground and reduce water flow above thesurface so that it can protect the soil from damage caused by erosion, obtained three(3) potential land suitability classes, namely : (1) land suitability S1 class (verysuitable) on land units V1 (LaIIKl), V3 (LaIKl) and V4 (LaIIIKl) land area of 1.450ha (31,73 %); (2) land suitability S2eh class (quite suitable) on the land unit V5(LaIVKl) land area of 720 ha (15,75 %); and (3) land suitability S3eh class (marginalsuitable) on land units V2 (LaVKl), V6 (LaVIKl) and V7 (LaVKl) covering an areaof 2,400 ha (52,52 %) with limiting erosion hazard factors (eh) especially the slopefactor.With this research, the selection of the location of clove plantations isadjusted to the suitability of the land, on land units that area very suitable andmarginal according to the slope factors as a limitation.Keywords: Land suitability, physical characteristics of land, clove plants